Effect of Pretransplant Use of Calcimimetic on Parathyroid Function after Renal Transplantation - Kanako Bokuda; Satoshi Morimoto; Yasufumi Seki; Noriyoshi Takano; Atsuhiro Ichihara (International Journal of Endocrinology)
Objective. Persistence of hyperparathyroidism (HPT) after renal transplantation leads to undesirable outcomes such as increase in cardiovascular events, graft dysfunction, and increased mortality. Options for therapy include medical management with calcimimetic or operative management. The present study was undertaken to evaluate the natural history of HPT after renal transplantation and to determine risk factors for persistent HPT in the era of calcimimetic. Design. The study is a retrospective review of data from 74 consecutive patients who underwent renal transplantation at our institution from April 2011 to November 2019. Methods. The natural history of HPT after renal transplantation and associations between intact parathyroid hormone (PTH) level after transplantation and clinical variables such as age, sex, duration of pretransplant dialysis, and use of calcimimetic before transplantation were evaluated. Results. Intact PTH decreased after renal transplantation in most of the patients without receiving parathyroidectomy. Known risk factors of persistent HPT did not associate with intact PTH level after renal transplantation in patients who had been receiving calcimimetic before transplantation. Conclusion. In conclusion, we have found that HPT after renal transplantation could be managed successfully by medical treatments. When predicting the prognosis of HPT after transplantation, pretransplant use of calcimimetic should be taken into consideration.